Hemorrhagic Longitudinally Extensive Transverse Myelitis (LETM) as a First Presentation of Neuromyelitis Optica Spectrum Disorder (NMOSD): A Case Report and Literature Review - Shima Jahani; Fateme Jamshidi; Abdorreza Naser Moghadasi (Clinical Case Reports)
ABSTRACT Here we present a rare case of hemorrhagic longitudinally extensive transverse myelitis (LETM) as a first presentation of Neuromyelitis Optica Spectrum Disorder. Even though the patient received aggressive treatment, he showed no significant improvement. Our case highlights the importance of prompt intervention in the case of hemorrhagic myelitis and the diagnostic challenges of hemorrhagic LETM.